The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1080/09602011.2019.1678490
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based systematic review of cognitive rehabilitation, emotional, and family treatment studies for children with acquired brain injury literature: From 2006 to 2017

Abstract: This paper updates guidelines of effective treatments for children with acquired brain injury (ABI) by including new evidence found in recent years and by building upon evidence presented in 2007. A systematic search was conducted for articles published from 2006-2017. Full manuscripts describing treatments of children (post-birth to 18) with acquired brain injury were included if study was published in peer-reviewed journals and written in English. Two independent reviewers and a third, if conflicts existed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 90 publications
1
45
0
2
Order By: Relevance
“…Preliminary evidence suggests that multi-component cognitive interventions combining computerized repeated practice and strategy use instruction are promising for cognitive rehabilitation of children with acquired brain injury. [11][12][13] A recent systematic review on cognitive rehabilitation for children with acquired brain injury showed that evidence for the use of technology in providing cognitive rehabilitation is increasing. 11 Specifically, cognitive functions are trained with technological interventions such as computerized repeated practice, meaning repeated practice of computer games (also sometimes referred to as "brain training" or "drill-based training").…”
Section: Rationale For Brainlevelmentioning
confidence: 99%
See 2 more Smart Citations
“…Preliminary evidence suggests that multi-component cognitive interventions combining computerized repeated practice and strategy use instruction are promising for cognitive rehabilitation of children with acquired brain injury. [11][12][13] A recent systematic review on cognitive rehabilitation for children with acquired brain injury showed that evidence for the use of technology in providing cognitive rehabilitation is increasing. 11 Specifically, cognitive functions are trained with technological interventions such as computerized repeated practice, meaning repeated practice of computer games (also sometimes referred to as "brain training" or "drill-based training").…”
Section: Rationale For Brainlevelmentioning
confidence: 99%
“…[11][12][13] A recent systematic review on cognitive rehabilitation for children with acquired brain injury showed that evidence for the use of technology in providing cognitive rehabilitation is increasing. 11 Specifically, cognitive functions are trained with technological interventions such as computerized repeated practice, meaning repeated practice of computer games (also sometimes referred to as "brain training" or "drill-based training"). 11 Computerized repeated practice is a non-invasive training approach in which patients repeatedly play specific computer games that have been specifically developed to improve cognitive functioning.…”
Section: Rationale For Brainlevelmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, an individualized approach to TBI management is recommended with the type and extent of academic modifications being variable based on the type and severity of symptoms, specific teaching style of each teacher the student encounters, and necessary environmental modifications. 1,13,31 A recent systematic review of intervention approaches that can be used in pediatric TBI 40 identified a variety of practice standards and guidelines that are useful for the SLP working with this population. For example, there is strong evidence for the inclusion of the family/caregiver in the intervention process, 41 for the role of education and training of teachers and school staff regarding the impact of a particular student's TBI, 42 and for the use of technology to support cognitive functions via alarms, reminders, and calendars.…”
Section: The Role Of the Slp In Treating Students With Tbimentioning
confidence: 99%
“…Hieronder vallen onder andere een stabiele gezinssituatie, mentaal welzijn en emotionele vaardigheden, maar ook basisbehoeften om adequaat cognitief te kunnen functioneren, zoals visuele en auditieve ondersteuning (bijvoorbeeld met een bril of een gehoorapparaat). Twee recente overzichtsstudie hebben aangetoond dat het betrekken van ouders, verzorgers of het hele gezin bij de cognitieve revalidatie van kinderen en jongeren met NAH belangrijk zijn voor het succes van de behandeling [17,18]. Behandelaren voor kinderen en jongeren met NAH moeten daarom aandacht besteden aan deze niet-cognitieve factoren en, indien relevant, deze gedurende de revalidatiebehandeling blijven monitoren.…”
Section: Cognitieve Revalidatieunclassified